Perfusion Assessment in Left-Sided/Low Anterior Resection (PILLAR III): A Randomized, Controlled, Parallel, Multicenter Study Assessing Perfusion Outcomes With PINPOINT Near-Infrared Fluorescence Imaging in Low Anterior Resection. Issue 8 (August 2021) - Jafari, Mehraneh D.; Pigazzi, Alessio; McLemore, Elisabeth C.; Mutch, Matthew G.; Haas, Eric; Rasheid, Sowsan H.; Wait, Alyssa D.; Paquette, Ian M.; Bardakcioglu, Ovunc; Safar, Bashar; Landmann, Ron G.; Varma, Madhulika G.; et al.
Abstract : BACKGROUND: Indocyanine green fluoroscopy has been shown to improve anastomotic leak rates in early phase trials. OBJECTIVE: We hypothesized that the use of fluoroscopy to ensure anastomotic perfusion may decrease anastomotic leak after low anterior resection. DESIGN: We performed a 1:1 randomized controlled parallel study. Recruitment of 450 to 1000 patients was planned over 2 years. SETTINGS: This was a multicenter trial. PATIENTS: Included patients were those undergoing resection defined as anastomosis within 10 cm of the anal verge. INTERVENTION: Patients underwent standard evaluation of tissue perfusion versus standard in conjunction with perfusion evaluation using indocyanine green fluoroscopy. MAIN OUTCOME MEASURES: Primary outcome was anastomotic leak, with secondary outcomes of perfusion assessment and the rate of postoperative abscess requiring intervention. RESULTS: This study was concluded early because of decreasing accrual rates. A total of 25 centers recruited 347 patients, of whom 178 were randomly assigned to perfusion and 169 to standard. The groups had comparable tumor-specific and patient-specific demographics. Neoadjuvant chemoradiation was performed in 63.5% of perfusion and 65.7% of standard ( p > 0.05). Mean level of anastomosis was 5.2 ± 3.1 cm in perfusion compared with 5.2 ± 3.3 cm in standard ( p > 0.05). Sufficient visualization of perfusion was reported in 95.4% of patients in the perfusion group. Postoperative abscess requiring surgical management was reported in 5.7% of perfusion and 4.2% of standard ( p = 0.75). Anastomotic leak was reported in 9.0% of perfusion compared with 9.6% of standard ( p = 0.37). On multivariate regression analysis, there was no difference in anastomotic leak rates between perfusion and standard (OR = 0.845 (95% CI, 0.375–1.905); p = 0.34). LIMITATIONS: The predetermined sample size to adequately reduce the risk of type II error was not achieved. CONCLUSIONS: Successful visualization of perfusion can be achieved with indocyanine green fluoroscopy. However, no difference in anastomotic leak rates was observed between patients who underwent perfusion assessment versus standard surgical technique. In experienced hands, the addition of routine indocyanine green fluoroscopy to standard practice adds no evident clinical benefit. See Video Abstract at http://links.lww.com/DCR/B560 . VALORACIÓN DE LA IRRIGACIÓN DE LADO IZQUIERDO/RESECCIÓN ANTERIOR BAJA (PILAR III ): UN ESTUDIO ALEATORIZADO, CONTROLADO, PARALELO Y MULTICÉNTRICO QUE EVALÚA LOS RESULTADOS DE LA IRRIGACIÓN CON PINPOINT IMÁGENES DE FLUORESCENCIA CERCANA AL INFRARROJO EN LA RESECCIÓN ANTERIOR BAJA: ANTECEDENTES: Se ha demostrado que la fluoroscopia con verde de indocianina mejora las tasas de fuga anastomótica en ensayos en fases iniciales. OBJETIVO: Nuestra hipótesis es que la utilización de fluoroscopia para asegurar la irrigación anastomótica puede disminuir la fuga anastomótica luego de una resección anterior baja. DISEÑO: Realizamos un estudio paralelo, controlado, aleatorizado 1:1. Se planificó el reclutamiento de 450-1000 pacientes durante 2 años. AMBITO: Multicéntrico. PACIENTES: Pacientes sometidos a resección definida como una anastomosis dentro de los 10cm del margen anal. INTERVENCIÓN: Pacientes que se sometieron a la evaluación estándar de la irrigación tisular contra la estándar en conjunto con la valoración de la irrigación mediante fluoroscopia con verde indocianina. PRINCIPALES VARIABLES EVALUADAS: El principal resultado fue la fuga anastomótica, y los resultados secundarios fueron la evaluación de la perfusión y la tasa de absceso posoperatorio que requirió intervención. RESULTADOS: Este estudio se cerró anticipadamente debido a la disminución de las tasas de acumulación. Un total de 25 centros reclutaron a 347 pacientes, de los cuales 178 fueron, de manera aleatoria, asignados a perfusión y 169 a estándar. Los grupos tenían datos demográficos específicos del tumor y del paciente similares. Recibieron quimio-radioterapia neoadyuvante el 63, 5% de la perfusión y el 65, 7% del estándar ( p > 0, 05). La anastomosis estuvo en un nivel promedio de 5, 2 + 3, 1 cm en perfusión en comparación con 5, 2 + 3, 3 cm en estándar ( p > 0, 05). Se reportó una visualización suficiente de la perfusión en el 95, 4% de los pacientes del grupo de perfusión. El absceso posoperatorio que requirió tratamiento quirúrgico fue de 5, 7% de los perfusion y en el 4, 2% del estándar ( p = 0, 75). Se informó fuga anastomótica en el 9, 0% de la perfusión en comparación con el 9, 6% del estándar ( p = 0, 37). En el análisis de regresión multivariante, no hubo diferencias en las tasas de fuga anastomótica entre la perfusión y el estándar (OR 0, 845; IC del 95% (0, 375; 1, 905); p = 0, 34). LIMITACIONES: No se logró el tamaño de muestra predeterminado para reducir satisfactoriamente el riesgo de error tipo II. CONCLUSIÓN: Se puede obtener una visualización adecuada de la perfusión con ICG-F. Sin embargo, no se observaron diferencias en las tasas de fuga anastomótica entre los pacientes que se sometieron a evaluación de la perfusión versus la técnica quirúrgica estándar. En manos expertas, agregar ICG-F a la rutina de la práctica estándar no agrega ningún beneficio clínico evidente. Consulte Video Resumen en http://links.lww.com/DCR/B560 . (Traducción—Dr Juan Antonio Villanueva-Herrero ) Abstract : Supplemental Digital Content is available in the text.